2016
DOI: 10.1136/heartjnl-2016-309806
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary risk estimates of three HbA1cvariables in relation to heart failure following diagnosis of type 2 diabetes

Abstract: BackgroundWe evaluated the association between glycaemic control and the risk of heart failure (HF) in a contemporary cohort of persons followed after diagnosis of type 2 diabetes (T2D).Methods and resultsPersons with T2D diagnosed between 1998 and 2012 were retrieved from the Clinical Practice Research Data Link in the UK and followed from diagnosis until the event of HF, mortality, drop out from the database due to any other reason, or the end of the study on 1 July 2015. The association between each of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
(28 reference statements)
0
6
0
1
Order By: Relevance
“…Clinical mod- els of cardiovascular risk assessment demonstrated similar modest levels of risk prediction. [32][33][34][35] Therefore, despite relatively modest effect size, flortaucipir scan patterns may provide clinically relevant prognostic information for AD patient management. Although statistical significance was not met for all tests, data for each study similarly showed that the advanced AD pattern group was at an increased risk of clinical progression.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical mod- els of cardiovascular risk assessment demonstrated similar modest levels of risk prediction. [32][33][34][35] Therefore, despite relatively modest effect size, flortaucipir scan patterns may provide clinically relevant prognostic information for AD patient management. Although statistical significance was not met for all tests, data for each study similarly showed that the advanced AD pattern group was at an increased risk of clinical progression.…”
Section: Discussionmentioning
confidence: 99%
“…This is partly because all the major risk factors for heart failure can present in patients with type 2 diabetes such as obesity, hypertension, advanced age, sleep apnoea, dyslipidaemia, anemia, chronic kidney disease, and coronary heart disease [15]. Hyperglycaemia is a risk factor for heart failure in persons with type 2 diabetes [16]. Excess body weight, is also a major risk factor for cardiovascular disease [17].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Heart , Skrtic and colleagues1 evaluated data from over 94 thousand primary care patients with type 2 diabetes (T2D) in the Clinical Practice Research Data Link to study the relationship between incident heart failure (HF) and hemoglobin A1c (HbA1c) levels at the initial diagnosis (baseline), most recent visit (updated latest) and an updated mean level. As shown in figure 1, elevations in all 3 HbA1c levels were associated with a higher hazard ratio  for HF, with the strongest association seen for the updated mean value.…”
mentioning
confidence: 99%